1958
DOI: 10.1099/00221287-19-3-522
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Extracellular and Intracellular Bacterial Deoxyribonucleic Acids

Abstract: SUMMARY : Highly polymerized bacterial deoxyribonucleic acids (DNAs) obtained from extracellular and from intracellular locations were analysed. DNAs from two strains (Staphylococcus aureus and S. epidermidis) were of the type having high adenine and thymine contents ; two others (Alcaligenes faecalis and Pseudomonas fluorescens) had a high content of guanine and cytosine. For each micro-organism the composition of extracellular DNA was essentially the same as that of the intracellular DNA. Conditions associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Studies in the 1950's identified eDNA as the major component of the slimy pellicle produced by a variety of different bacteria including Actinomyces viscosus [37,38]. Even at such an early stage, it was speculated that eDNA may play roles in addition to the carriage of genetic information between cells, such as protection against desiccation or radiation, avoiding overcrowding or slowing the movement of cations towards cells [38].…”
Section: Functions Of Edna In Biofilmsmentioning
confidence: 99%
“…Studies in the 1950's identified eDNA as the major component of the slimy pellicle produced by a variety of different bacteria including Actinomyces viscosus [37,38]. Even at such an early stage, it was speculated that eDNA may play roles in addition to the carriage of genetic information between cells, such as protection against desiccation or radiation, avoiding overcrowding or slowing the movement of cations towards cells [38].…”
Section: Functions Of Edna In Biofilmsmentioning
confidence: 99%
“…Organisms were lysed with sodium dodecylsulphate, as described . The DNA-containing fibrous masses obtained by precipitation with 2 volumes of ethanol were purified by methods (Catlin & Cunningham, 1958; which included two separate steps of deproteinization with sodium dodecylsulphate; each was followed by a step involving centrifugation of the DNA solution (in M-NaCl) for 110 min. (32,OOOg; 3"), and precipitation of DNA fibres with ethanol.…”
Section: Transformation Of Various Neisseriae 305mentioning
confidence: 99%
“…In addition, the organism has the unique biological character of producing large amounts of DNA which accumulates extracellularly (7,16). The occurrence of extracellular DNA has also been reported for Neisseria (2), Bacillus subtilis (15), Pseudomonas fluorescens (7), Vibrio parahaemolyticus (7), Staphylococcus aureus (3), Staphylococcus epidermidis (3), and Alcaligenes faecalis (3). Moreover, transformation by extracellular DNA has been demonstrated in Neisseria (2), Streptococcus (12), and B. subtilis (14).…”
mentioning
confidence: 99%